Coating of polylactide films by chitosan: Comparison of methods. Issue 3 (24th July 2019) - Demina, Tatiana S.; Frolova, Anastasia А.; Istomin, Alexander V.; Kotova, Svetlana L.; Piskarev, Mikhail S.; Bardakova, Ksenia N.; Yablokov, Mikhail Y.; Altynov, Vladimir A.; Kravets, Liubov I.; Gilman, Alla B.; Akopova, Tatiana A.; Timashev, Peter S.
ABSTRACT: Control over biomaterials surface characteristics through surface modification or deposition of coatings is one of the key aspects of tissue engineering. This work was aimed to evaluate an effectiveness of various methods of chitosan‐coating formations onto polylactide films using a number of techniques, such as vacuum deposition by electron‐beam sputtering, chemical entrapment method, and electrospray procedure. Differently coated films were studied in terms of surface morphology (scanning electron and atomic‐force microscopy), chemical structure (FTIR and X‐ray photoelectron spectroscopy), and hydrophilic/hydrophobic balance (goniometry). The effect of coating technique on homogeneity of chitosan distribution over the substrate surface was evaluated using genipin and fluorescein isothiocyanate labeling as well as FTIR‐microscopy. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48287. Abstract :